2013
DOI: 10.4103/0257-7941.139042
|View full text |Cite
|
Sign up to set email alerts
|

A self-rating scale to measure tridoṣas in children

Abstract: Background:Self – rating inventories to assess the Prakṛti (constitution) and personality have been developed and validated for adults. To analyze the effect of personality development programs on Prakṛti of the children, standardized scale is not available. Hence, present study was carried out to develop and standardize Caraka Child Personality inventory (CCPI).Materials and Methods:The 77- item CCPI scale was developed on the basis of translation of Sanskrit verses describing vātaja (a), pittaja (b) and kaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the recent past there is a growing research interest in studying prakriti in an objective manner with the help of prakriti assessment tools [9] as Ayurvedic physicians have agreed the need for research based standardized tool for prakriti assessment [10] . The standardized questionnaires such as Sushrutha Prakriti Inventory (SPI) [11] , Caraka Child Personality Inventory [12] , Mysore Tridosha Scale [13] have shown significant results in prakriti assessment. Recent studies on genetics with help of prakriti questionnaires have shown that prakriti and genes are closely associated which emphasizes the significance of questionnaires in assessing prakriti [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past there is a growing research interest in studying prakriti in an objective manner with the help of prakriti assessment tools [9] as Ayurvedic physicians have agreed the need for research based standardized tool for prakriti assessment [10] . The standardized questionnaires such as Sushrutha Prakriti Inventory (SPI) [11] , Caraka Child Personality Inventory [12] , Mysore Tridosha Scale [13] have shown significant results in prakriti assessment. Recent studies on genetics with help of prakriti questionnaires have shown that prakriti and genes are closely associated which emphasizes the significance of questionnaires in assessing prakriti [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%